Pekerja Anak dan Solusi dari Sudut Pandang Syariat - Sabirin Sabirin (PSGA LP2M IAIN Pontianak, 2019)
The emergence of child labor for various reasons, such as economic, motivation and cultural influences. In addition, children choose, are asked, even to work with classical reasons such as addressing the problem of poverty, the encouragement of the family itself and the environmental influences that have made the children choose to work. The impact of working at an early age greatly endangers the development of children. Dangerous things that could arise and should be accepted children who work together with health, safety, moral and psychological development of children. Because working with long working hours, and low wages, and frequent exploitation because children do not have the opportunity to enjoy education, affection from parents, and playing to enjoy childhood. The concept of maqashid al-Shari'ah is handed down from five things: the strengthening of the religion (ad-din) of the child, the soul (an-naf), the child of reason (al-aql), the offspring (an-nas) malls) for children. If we are especially Muslims back on these five things, then pekeja children of course with many things will be reduced, even abolished. Although child labor can help the family, for the sake of survival, this must continue to remember madaratnya greater than maslahatnya.